Association between pacifier use and bottle-feeding and unfavorable behaviors during breastfeeding - Christyann L.C. Batista; Valdinar S. Ribeiro; Maria do Desterro S.B. Nascimento; Vandilson P. Rodrigues (Elsevier, 2018)
Objective: To investigate the association between pacifier use and bottle-feeding and unfavorable behaviors during breastfeeding. Method: A cross-sectional study was conducted with 427 babies/mothers. Socio-demographic, perinatal data, and information about the use of artificial nipples (pacifier and/or bottle) were collected through a questionnaire. The breastfeeding aspects regarding position, affectivity, sucking behavior, baby responses, and breast anatomy were evaluated through observation during breastfeeding. The chi-squared test and the multiple linear regression analysis were used to investigate the association between the variables. Results: The aspects of breastfeeding that showed higher percentages of the category "poor" were sucking behavior (22.5%) and position (22.2%). The group of infants who used pacifiers and/or bottle showed higher percentages in the poor and fair categories when compared with the good category for all five breastfeeding aspects evaluated (p < 0.001). The linear regression analysis revealed that the increase in the number of unfavorable behaviors regarding position, affectivity, sucking behavior, and baby responses were independently associated with both pacifier and bottle use (β positive, p < 0.05), while breast anatomy was independently associated only with bottle use. Conclusion: The findings suggest that the use of pacifiers and/or bottle-feeding may be associated with unfavorable behaviors during breastfeeding, especially the use of bottle-feeding. Resumo: Objetivo: Investigar a associação entre uso de chupeta e mamadeira e comportamentos desfavoráveis à amamentação durante as mamadas. Métodos: Um estudo transversal foi conduzido com 427 bebês/mães. Foram coletados dados sociodemográficos, perinatais e sobre o uso de bicos artificiais (chupeta e/ou mamadeira) através de questionário. Os aspectos de amamentação referentes à posição, afetividade, adequação da sucção, respostas do bebê e anatomia das mamas foram avaliados através da observação durante a mamada. O teste qui-quadrado e a análise de regressão linear múltipla foram usados para investigar associação entre as variáveis. Resultados: Os aspectos de amamentação que apresentaram percentuais mais elevados da categoria ruim foram a adequação da sucção (22,5%) e posição (22,2%). O grupo de bebês que usavam chupeta e/ou mamadeira apresentou percentuais mais elevados nas categorias ruim e regular quando comparados com a categoria bom para todos os cinco aspectos da amamentação avaliados (p < 0,001). A análise de regressão linear revelou que o incremento do número de comportamentos desfavoráveis referentes à posição, afetividade, adequação da sucção e respostas do bebê estavam associados de forma independente tanto ao uso de chupeta quanto ao uso de mamadeira (β positivo, p < 0,05), enquanto que anatomia das mamas estava associado de forma independente apenas com o uso de mamadeira. Conclusão: Os achados sugerem que o uso de chupeta e/ou mamadeira pode estar associado a comportamentos desfavoráveis durante amamentação, em especial, o uso de mamadeira. Keywords: Breastfeeding, Pacifiers, Bottle-feeding, Palavras-chave: Amamentação, Chupetas, Uso de mamadeira